Enhancing Digital Skills and Visual Innovation through Cloud-Based Design Platforms among Vocational Education Students - Jusbaeni Jusbaeni; Umara Hasmarani Rizqiyah; Firnawati Firnawati; Dewi Satriyati Ninsyi; Siti Asmaulul Izmi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
This community engagement program aims to enhance digital competencies and visual innovation skills among students in vocational education institutions through training using cloud-based graphic design platforms. In the era of digital transformation, the ability to produce effective visual content has become essential for supporting communication, learning activities, and creative entrepreneurship. The program was delivered through an intensive workshop covering fundamental principles of graphic design, visual communication, and hands-on practice in creating digital media using an online design application. Demonstration-based learning and direct mentoring were employed to ensure participants developed strong understanding of layout, color theory, typography, and visual composition. The results indicate significant improvements in participants’ ability to produce informative, visually appealing, and communication-oriented designs. Additionally, the training fostered creativity, digital literacy, and confidence in utilizing design technology for academic purposes and potential entrepreneurial initiatives. These findings highlight that cloud-based design tools offer an effective strategy for strengthening 21st-century competencies within vocational education settings.